The Protective Effects of Different-Time-Ischemic Preconditioning on the Reperfusion Injury in Fatty Livers in Rats - Jiang, Yong (Public Library of Science, 2013)
BACKGROUND: The present study was aimed to investigate the protective effects of different-time-ischemic preconditioning on the reperfusion injury in fatty livers in rats, and to elucidate the mechanisms underlying the protective effects and the optimal safe ischemic preconditioning time on the hepatic IR injury in steatotic livers. METHODOLOGY/PRINCIPAL FINDINGS: A rat fatty liver model was established by high-fat diet feeding. We investigated the changes in the concentration of AST, ALT, LDH and NO in the serum, and of MDA, SOD, and MPO in the liver samples in response to different ischemic preconditioning times and ischemia-reperfusion injury. Histological analysis was performed to evaluate the results of the hepatic fatty infiltration. 1) At 24 h after 15 min ischemic preconditioning with 10 min reperfusion (15 min +10 min IP), the extent and area of the necrosis was markedly higher in the fatty liver samples with respect to IR, compared to the normal liver samples. 2) In response to the treatment of 5/8 min +10 min IP, the fatty liver group showed lower levels of serological indicators and liver MDA and MPO compared to the other groups, while the SOD activity of the fatty liver group was significantly higher than the other groups (p<0.05). Compared to the corresponding IR group, all IP groups showed a significantly higher serum NO concentration (p<0.05). Among the fatty liver groups, the 5/8 min+10 min IP group showed the highest NO concentration (p<0.05). CONCLUSIONS/SIGNIFICANCE: Fat infiltration could aggravate the ischemia-reperfusion injury in the rat liver. Furthermore, ischemic preconditioning could increase the tolerance of the fatty liver, which was induced by the high-fat diet, to hepatic ischemia-reperfusion injury in rats. The protocol of 5/8 min +10 min IP was the optimal regimen for the treatment of moderate and severe fatty livers.